Migratory Polyarthritis Associated With Clopidogrel: A Case Report - Hamid Khederlou; Reza Hassanzadeh-Makoui; Vanoushe Azimi Pirsaraei (Acta Medica Iranica)
Clopidogrel, a selective thienopyridine, is used for secondary prevention of major adverse cardiovascular events. Some studies have reported inflammatory arthritis as a rare adverse effect of Clopidogrel. A 47-year-old male underwent percutaneous coronary intervention and was subsequently prescribed a 600 mg loading dose of Clopidogrel, followed by a daily dose of 75 mg. After six days of taking Clopidogrel, the patient presented to the emergency department with right knee pain. The knee joint exhibited swelling, warmth, and tenderness, although there was no redness or crusting. After two and six days of hospitalization, despite receiving antibiotics and Indomethacin, he developed arthritis of the metacarpophalangeal and metatarsophalangeal joints, respectively. According to the laboratory investigation, cultures, synovial fluid analysis, and imaging, infectious, rheumatologic, and crystallopathy diseases were ruled out for the patient. Clopidogrel was discontinued, and the patient was switched to ticagrelor 90 mg twice daily. All symptoms and signs of joint inflammation had improved within five days of stopping the Clopidogrel. After one week and one and six months of follow-up, there has been no recurrence of symptoms.